Maritime Discourse as part of Professional Discourse : Array - Berlinskyi , Yurii (Journal of Danubian Studies and Research, 2021)
The purpose of the article is to analyze the existing views on professional discourse in linguistics and highlight the concept of maritime discourse in it. The material analyzes such key concepts as discourse, professional discourse and maritime discourse. The key approach to writing a work is diachronic, which manifests itself in the study of the works of linguists on this issue. The article summarizes the scattered views of scientists on the maritime discourse as part of the professional in one system, on the basis of which it is possible to study the key features of the maritime discourse. The value of the article is presented in the form of a theoretical generalization of different views on the concept of maritime discourse for understanding this phenomenon at the present stage of development of cognitive linguistics.